2022
DOI: 10.1089/heq.2022.0079
|View full text |Cite
|
Sign up to set email alerts
|

Socially Assigned Race and the Health of Racialized Women and Their Infants

Abstract: Introduction: While historically most public health research has relied upon self-identified race as a proxy for experiencing racism, a growing literature recognizes that socially assigned race may more closely align with racialized lived experiences that influence health outcomes. We aim to understand how women's health behaviors, health outcomes, and infant health outcomes differ for women socially assigned as nonwhite when compared with women socially assigned as white in Massachusetts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The studies found that the prevalence of smoking among pregnant MENA women ranged from < 1-6% compared to 12-16% among pregnant White women (Abuelezam et al, 2020;El Reda et al, 2007;Johnson et al, 2005;Kulwicki et al, 2007). One study found that prevalence estimates of smoking during or within three months before pregnancy were 6-10% among MENA women (Abuelezam et al, 2022). However, this study did not make any comparisons in smoking to White women.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The studies found that the prevalence of smoking among pregnant MENA women ranged from < 1-6% compared to 12-16% among pregnant White women (Abuelezam et al, 2020;El Reda et al, 2007;Johnson et al, 2005;Kulwicki et al, 2007). One study found that prevalence estimates of smoking during or within three months before pregnancy were 6-10% among MENA women (Abuelezam et al, 2022). However, this study did not make any comparisons in smoking to White women.…”
Section: Introductionmentioning
confidence: 73%
“…There is a growing body of literature focused on outcomes among MENA women and children (Abuelezam et al, 2022;. Yet, the existing MCH literature among MENA women and children fails to address national objectives and performance measures (Berge et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Abuelezam and colleagues (2022) used data from the Massachusetts Pregnancy Risk Assessment Monitoring System (PRAMS) to evaluate the health of MENA mothers and their children based on socially assigned race. The study evaluated several women's health behaviors, including initiating prenatal care during the rst trimester, breastfeeding in the hospital, and abstaining from alcohol three months prior and during pregnancy (Abuelezam et al, 2022). However, the study did not assess whether women saw a dentist in the last six months.…”
Section: Discussionmentioning
confidence: 99%
“…Conducting refugee health research is particularly challenging because few public health systems collect data on migration history and experiences. Refugee populations are often studied within their racial and ethnic groups without inquiry into their displacement history or considering race as a social construct . Designing novel health interventions to address health disparities in the minoritized refugee population requires a deep understanding of various contextual factors such as wars or other trauma exposure in the country of origin, experiences during migration, resettlement community politics and capacities, education level, and social support systems, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Refugee populations are often studied within their racial and ethnic groups without inquiry into their displacement history or considering race as a social construct. 19 , 20 , 21 , 22 Designing novel health interventions to address health disparities in the minoritized refugee population requires a deep understanding of various contextual factors such as wars or other trauma exposure in the country of origin, experiences during migration, resettlement community politics and capacities, education level, and social support systems, among others. Refugee health research is needed to assess these interplaying factors and formulate evidence-based recommendations allowing for achieving optimal health over the life course.…”
Section: Introductionmentioning
confidence: 99%